The Effect of Family-Centered Empowerment in Self Efficacy and Self Esteem in Patients Undergoing Coronary Bypass Graft Surgery - Neda Sanaie; Soraya Nejati; Mitra Zolfaghari; Fatemeh Alhani; Anooshiravan KazemNejad (Golestan University of Medical Sciences, 2013)
Background and objective: Coronary Bypass Graft Surgery (CBG) is one of the therapeutic approaches having the leading effects on the function of the patients. Because of paramount importance of self-efficacy and self-esteem, we aimed to evaluate the effectiveness of family-centered empowerment on the self- efficacy and self-esteem of the patients undergoing coronary bypass surgery. Material and Methods: This case control clinical trial was conducted on 102 patients with elective heart surgery and 102 of their active family members in 2011.‌ The patients were selected via convenience sampling and randomly assign ed to experimental and control group. After measuring the self-efficacy and self-esteem, family-centered empowerment care, including individual training, group discussion, film and active participation,‌ was performed in experimental and just routine care in control group. Using PASW statistics-18, we analyzed the data. Results: The results showed that the two groups were the same considering population variables and the mean scores of self-efficacy and self-esteem. The level of self-efficacy and self-esteem in case group were significantly higher than those of controls (P<0.000). After intervention, the mean score of self-efficacy and self-esteem were increased (P<0.0000). Conclusion:‌In regard with the results,‌ family-centered ‌empowerment care ‌in patients undergoing CBG is practically feasible , and it can be helpful in improving self-efficacy and self- esteem.